Endothelial function in hypercholesterolemic subjects: Effects of plant stanol and sterol esters - Hallikainen, Maarit; Lyyra-Laitinen, Tiina; Laitinen, Tomi; Ågren, Jyrki J.; Pihlajamäki, Jussi; Rauramaa, Rainer; Miettinen, Tatu A.; Gylling, Helena (Atherosclerosis, 2006)
We investigated the effects of stanol (STAEST) and sterol esters (STEEST) on endothelial function in hypercholesterolemic subjects. In addition, associations of variables of cholesterol metabolism with endothelial function were investigated. In a double-blind randomized cross-over study ( n = 39) with age-matched parallel control group ( n = 37) the subjects consumed STAEST or STEEST spread (total plant sterols and stanols 1.93–1.98 g/day) for 10 weeks each. Controls consumed the spread without sterols or stanols for 20 weeks. At baseline, brachial artery diameter was positively correlated with serum triglycerides ( r = 0.375, p = 0.001) and glucose ( r = 0.420, p < 0.001) and with cholesterol synthesis marker ratios to cholesterol (e.g. desmosterol r = 0.540, p < 0.001) and negatively with HDL cholesterol ( r = −0.309, p = 0.008) and absorption marker ratios (e.g. campesterol r = −0.332, p = 0.004). During the intervention, LDL cholesterol was reduced by 6–9% from baseline with STAEST and STEEST spreads ( p < 0.05), and by 9–12%, respectively, from controls ( p < 0.05). Flow-mediated dilatation did not change during the investigation. Brachial artery diameter was unchanged in controls and during STAEST periods, but it was reduced during STEEST by 2.2% ( p = 0.012) from STAEST. In conclusion, variables of cholesterol metabolism are associated with brachial artery diameter at baseline. STEEST diminishes brachial artery diameter, but its clinical relevance remains unclear.